POLA ASUH ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK MELALUI PEMBELAJARAN HIKMAT DARI SEMUT MENURUT AMSAL 6:6-11 - Siburian, Rudi; Tampilang, Petra Harys Alfredo; Simbolon, Andreas Kongres P. (Jurnal Teologi RAI, 2024)
The book of Proverbs is a collection of wise sayings or wisdom that should be pondered and applied in life. Wisdom itself can be obtained through learning from teachers of wisdom and the upbringing and example of parents and by living wisely, one should have a better life, and achieve success. But what happens in Proverbs 6:1-11 is the opposite, the child becomes entangled in his words (verse 2), falls into the grasp of others or debt (verse 3), is labeled lazy (verse 6) and finally becomes poor (verse 11). Looking at the above problems, the question arises: "Why does the writer of Proverbs advise children to learn from the lives of ants? Was the wisdom of the teachers of wisdom and the parenting of the parents at that time no longer able to shape the character of the child to live better and think about his future? This is what the author is interested in discussing. So, to overcome the above problems, it is necessary to apply the right (biblical) parenting to children and learn wisdom by paying attention to good things in the surrounding environment such as the way ants live. So that children can avoid laziness, and poverty and can achieve success in the future according to their God-given potential. In researching Proverbs 6:6-11, the author used a qualitative descriptive method through the sources of wisdom books, commentaries, journals, the Bible, dictionaries, and other books. Through this research, it was found that there are three parenting patterns in shaping children's character through learning wisdom from ants, namely: First, avoiding laziness. Second, hard work and discipline. Third, wise time management.